Taxonomic listing of mangrove species in Sapa Taklong, Taklong Island, Nueva Valencia, Guimaras. - Pedregosa, Angelie Donato
The species found in SapaTaklong, Taklong Island, Nueva Valencia, Guimaras were taxonomically listed and the area covered by mangroves was investigated in the study. There are 13 species of true mangroves found in the area around Sapa Taklong. The species are Acanthus ilicifolius (Acanthaceae); Avicennia marina and A. rumphiana(Avicenniaceae); Lumnitzera racemosa (Combretaceae); Xylocarpus granatum (Meliaceae); Aegiceras floridum (Myrsinaceae); Osbornia octodonta (Myrtaceae); Nypa fruiticans (Palmae); Rhizophora apiculata, R. mucronata, and C. tagal (Rhizophoraceae); and Sonneratia alba (Sonneratiaceae). The results of the study suggest that Sapa Taklong has a good diversity of mangrove species.